SIKLUS EVOLUSI PARIWISATA ASMAT DAN PERILAKU TURIS DALAM KONTEKS ETHNIC TOURISM - Kurniawan, Ramdhan; Suhud, Usep; Kosasih, Fauzy Rahman; Putra, Octavia Basuki (ITB AAS Indonesia Surakarta, 2024)
Asmat is one of the tribes and districts in Papua which has long been a tourism destination for domestic and foreign tourists. This research focuses on ethnic tourism and aims to explore the tourism destination evolutionary cycle and host perceptions of tourism development in the setting of the Asmat ethnic community in Papua. Apart from that, this research also aims to examine the factors that influence tourists' intentions to visit Asmat destinations. This research uses two approaches, qualitative and quantitative. Data was collected through observation, interviews and surveys. Meanwhile, the data is processed using content analysis for qualitative data, and multiple regression analysis for quantitative data.